(untitled) - Dufeu, Bernard (Oxford, 1995)
This book starts with a presentation of an approach to foreign language acquisition through the use of psychodrama techniques and proposes a new methodology pf foreign language teaching. The second, and main part of the book, focuses on a wide range of practical ways for experiencing the language from within: relaxation techniques, means of acquiring the intonation and rhythm of a foreign language, and communicative exercises oriented towards participant development. It also intriduces ways of using fairy-tales and myths in the classroom. The last part of the book deals with teacher development and considers how teacher relate to participants in their teaching
Keywords: language and languages; foreign speakers,study and teaching